Posterior Reversible Encephalopathy Syndrome as an Overlooked Complication of Induced Hypertension for Cerebral Vasospasm: Systematic Review and Illustrative Case. Issue 2 (February 2016) - Muhammad, Sajjad; Güresir, Ági; Greschus, Susanne; Scorzin, Jasmin; Vatter, Hartmut; Güresir, Erdem
Abstract : Background and Purpose—: Delayed cerebral ischemia associated with cerebral vasospasm is a common cause of secondary neurological decline after aneurysmal subarachnoid hemorrhage (SAH). Triple-H therapy, induced hypertension, hypervolemia, and hemodilution, is often used to treat cerebral vasospasm. However, hypertensive treatment may carry significant medical morbidity, including cardiopulmonary, renal, and intracranial complications. Posterior reversible encephalopathy syndrome (PRES) is a reversible intracranial complication that has rarely been reported in the setting of induced hypertension. Methods—: We present an illustrative case of PRES in a patient with induced hypertension for SAH-related cerebral vasospasm and performed a systematic review. Furthermore, the electronic database MEDLINE was searched for additional data in published studies of PRES after induced hypertension. Results—: Overall, 7 case reports presenting 10 patients who developed PRES secondary to induced hypertension were found. Eighty-two percent of the patients were women. In all cases, the clinical symptoms were attributed to cerebral vasospasm before the diagnosis of PRES. The time from onset of induced hypertension to the development of PRES was 7.8±3.8 days. After the diagnosis of PRES and careful taper down of the blood pressure, the neurological symptoms resolved almost completely within a few days in all patients. Conclusions—: PRES in the setting of SAH is an overlooked complication of hypertensive therapy for the treatment of vasospasm. However, the diagnosis of this phenomenon is crucial given the necessity to reverse hypertensive therapy, which is contrary to the usual management of patients with vasospasm.